Analisis Kinerja Reksa Dana Saham Konvensional dengan Metode Jensen’s Alpha, Sortino dan Snail Trail Periode 2017-2021 - Kertiani, Putu Tia; Masdiantini, Putu Riesty (Vokasi : Jurnal Riset Akuntansi, 2021)
This study aims to analyze the performance of conventional equity mutual funds using jensen's Alpha, Sortino, and Snail Trail methods for the period 2017 to 2021 and can provide information and consideration regarding equity mutual funds. The measurement methods used in analyzing the performance of conventional stock mutual funds are Jensen's Alpha, Sortino, and Snail Trail. The sample used was 32 conventional stock mutual funds with a period of 5 years 2017-2021. The benchmark for stock mutual funds used for comparison is JCI. The data collection technique uses the purposive sampling method.  Data analysis techniques in this study used the Mann Whitney U-test. The results showed that the performance of conventional equity mutual funds using Jensen's Alpha and Sortino methods had significant differences. The performance of conventional equity mutual funds using Jensen's Alpha and Sortino methods has significant differences and has superior performance compared to market performance. The results of snail trail show that the performance of conventional equity mutual funds is in quadrants 2 and 3. Equity mutual funds located in quadrant 2 have a relatively high value of return and risk and each stock mutual fund located in quadrant 3 has a relatively low return with high risk. The more often the snail trail of stock mutual funds is located in 3rd quarter, it is likely that investors will switch to other types of mutual funds.